2011
DOI: 10.1097/cad.0b013e328347181a
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid pristimerin synergizes with taxol to induce cervical cancer cell death through reactive oxygen species-mediated mitochondrial dysfunction

Abstract: A combined treatment with conventional chemotherapies can enhance the effectiveness of chemotherapeutic agents against cancers. Here, we have shown that the naturally occurring triterpenoids synergistically enhance the response of cervical cancer cells to taxol. Of the triterpenoid compounds, pristimerin enhanced the anticancer effect of taxol with the highest efficiency by combination. Pristimerin synergizes with taxol to inhibit clonogenic survival and tumor growth in nude mice, and to enhance cell death in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…It has long been used as an anti‐malarial, anti‐inflammatory, anti‐oxidant and insecticide 2,3 . Recent studies have shown that Pristimerin potently induced anti‐proliferative and apoptosis activities in several human cancer cell lines, which originated from lung, breast, prostate, glioma, cervical, leukaemia and multiple myeloma tumours 2,4‐8 . Induction of apoptotic cell death by Pristimerin involved with different mechanisms, including caspase activation, proteasomes inhibition, mitochondrial dysfunction and different molecular mechanisms involved in the suppression of anti‐apoptotic NF‐ÎșB, Akt and MAP kinases 9‐11 .…”
Section: Introductionmentioning
confidence: 99%
“…It has long been used as an anti‐malarial, anti‐inflammatory, anti‐oxidant and insecticide 2,3 . Recent studies have shown that Pristimerin potently induced anti‐proliferative and apoptosis activities in several human cancer cell lines, which originated from lung, breast, prostate, glioma, cervical, leukaemia and multiple myeloma tumours 2,4‐8 . Induction of apoptotic cell death by Pristimerin involved with different mechanisms, including caspase activation, proteasomes inhibition, mitochondrial dysfunction and different molecular mechanisms involved in the suppression of anti‐apoptotic NF‐ÎșB, Akt and MAP kinases 9‐11 .…”
Section: Introductionmentioning
confidence: 99%
“…gambogic acid, gambogic acid amide and tetragambogic acid). (16) Two other hit compounds, obutsaquinone (17) and pristimerin, (18) are also natural products. Only one of the hits, acriflavine, is a synthetic compound.…”
Section: Mechanistic Characterization Of Acriflavine Using Connectivitymentioning
confidence: 99%
“…Apoptosis can be initiated either by the mitochondria (the intrinsic pathway) or through cell death receptors (the extrinsic pathway), leading to the activation of caspase cascades and resulting in apoptosis. Previous studies have reported that pristimerin may induce cell apoptosis via both the mitochondria and the death receptor-mediated extrinsic pathways in U87 glioma cells (29) and cervical cancer cells (30). Pristimerin likewise modulates the levels of B-cell lymphoma 2 (Bcl-2) family proteins, which are known to be involved in mitochondria-mediated apoptosis, in pancreatic cancer cells (31).…”
Section: Discussionmentioning
confidence: 99%